COVID-19: Integrating the Complexity of Systemic and Pulmonary Immunopathology to Identify Biomarkers for Different Outcomes - Fraga-Silva, Thais Fernanda de Campos; Maruyama, Sandra Regina; Sorgi, Carlos Arterio; Russo, Elisa Maria de Sousa; Fernandes, Ana Paula Morais; de Barros Cardoso, Cristina Ribeiro; Faccioli, Lucia Helena; Dias-Baruffi, Marcelo; Bonato, Vânia Luiza Deperon (Frontiers in Immunology, 2021)
In the last few months, the coronavirus disease 2019 (COVID-19) pandemic has affected millions of people worldwide and has provoked an exceptional effort from the scientific community to understand the disease. Clinical evidence suggests that severe COVID-19 is associated with both dysregulation of damage tolerance caused by pulmonary immunopathology and high viral load. In this review article, we describe and discuss clinical studies that show advances in the understanding of mild and severe illness and we highlight major points that are critical for improving the comprehension of different clinical outcomes. The understanding of pulmonary immunopathology will contribute to the identification of biomarkers in an attempt to classify mild, moderate, severe and critical COVID-19 illness. The interface of pulmonary immunopathology and the identification of biomarkers are critical for the development of new therapeutic strategies aimed to reduce the systemic and pulmonary hyperinflammation in severe COVID-19.